ANALISIS KEBIJAKAN DALAM IMPLEMENTASI DESA ANTI KORUPSI DI TINGKATAN PEMERINTAH DESA TABONGO TIMUR - Arsjad, Muh. Fachri; Syukran, Muh.; Austin, Trecy; Tabo, Sarfan; Nuna, Muten S. (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to examine the implementation of the Anti-Corruption Village policy in East Tabongo Village, and explore the factors that support and hinder its implementation. The research method used is qualitative with a case study approach, where data is collected through in-depth interviews, observations, and documentation studies. The results of the study indicate that the East Tabongo Village government has adopted the principles of transparency, accountability, community participation, and community-based supervision in every aspect of financial management and public services. The success of the implementation of this policy is supported by the commitment of the village head, the active involvement of the Village Consultative Body (BPD), and the existence of ongoing training and socialization to the community. However, there are still a number of obstacles such as the low capacity of village officials, limited resources, and resistance of a small part of the community to change. The findings of this study emphasize the importance of strengthening village institutional capacity, increasing community legal literacy, and ongoing supervision to ensure the sustainability of the Anti-Corruption Village policy. This study provides a practical contribution in developing a clean, participatory, and integrity-based village governance model, and can be used as a reference in formulating anti-corruption policies in other villages in Indonesia